General principals of emergency poisoning treatment in the general practice office – challanges and obstacles - Lazarevic, Marija ž (General Practice, 2024)
Introduction. Timely recognition of acute or chronicpoisoning, as well as the pharmacodynamic mechanisms andpathophysiology of poisoning, is of the utmost importance inthe general practice office.Objective. We aimed to find out the rate of awarenessand education of primary healthcare physicians on necessarymeasures in the case of poisoning treatment.Method. Physicans working in general practice in theRepublic of Serbia were sent an electronic questionnaire ’’Urgentpoisoning treatment in the general practice office’’. Thequestionnaire had 13 questions referring to the physician’spractical experience.Results. The rise of medication, product, and biologicalsubstance poisoning rate was registered at the primaryhealthcare level in the last five years and it went from 0,14 to0,21. Poisoning with non-medical substances is on the steepdecline, from 0,30 to 0,19 per 1000 inhabitants. We followedthe experience of general physicians (GPs) from outpatientclinics, concerning the cases of acute and chronic poisoning,by examining the questionnaire which showed 71,43% ofGPs met with this condition. Physicans were more likely tobe met with accidental poisoning (41,07%), while (21,43%)were met with multiple intentional poisonings. A larger percentageof these cases (44,65%) were treated on-site. Aboutthe existence of the National Poisoning Control Center knew53,57% of physicans and 58,93% were familiar with detoxicationmeasures. Additional expertise in the area of poisoningis necessary in the opinion of 75% of physicians.Discussion. Poison intake, in different ways, into abody, may cause a patient’s death if not recognized on time,at the initial encounter in the general physician’s office.Conclusion. Awareness and education of the GPs inthe outpatient clinics, as well as, readiness to learn additionalskills proved to be an important factor in taking care of poisonedpatients who call on their GPs first. Continuous educationis a necessary measure for the improvement of healthcarequality in the treatment of acute and chronic poisoning.
Keywords: poisoning; general practice; acute treatment